Synthesis and Antimicrobial Activity of Newly Synthesized Substituted 3-flavanol - Utale, P.S.; Raghuwanshi, P.B.; Doshi, A.G. (Asian Journal of Chemistry, 2010)
2´-Hydroxy-5´-chlorochalcone and its derivatives react with H2O2 in presence of NaOH to give 6-chloro-3-flavanol and its derivatives. These synthesised compounds were tested against test organisms Staphylococcus aurecus, Staphylococous pyrogens, S. agalactiae, S. faecalis, Corynebacterium ulcerans, C. minutissimum, Clostridum septicum, Clostridium tetani and Escherichia coli. The % MIC values were determined by using serial dilution method.